In Search of a Sustainable Economy; Will Islamic Banking Help Nepal and ‎Nepali Muslims?‎ - SHAMIM, SAEMAH (International Journal of Islamic Economics and Governance, 2022)
This article attempts to shed light on the issue of "why Nepal should adopt Islamic banking." The research presented in this conceptual and theoretical work is based on a thorough review of the literature. This paper will begin with a discussion of why the current banking system needs to be updated or changed, followed by an examination of its characteristics and how it might benefit Nepal’s economy. The possibility of Islamic finance functioning as a microfinance tool by involving those who do not engage in economic activity will also be explored in this study. This article also argues for the need to set aside theological differences in order to embrace Islamic financing for the upliftment of underprivileged Muslim and non-Muslim minorities. Islamic finance has several advantages that cannot be dismissed based solely on the name or the notion that it is only for Muslims. To assist underprivileged populations in escaping poverty, Nepal’s economy requires a banking system that would operate for welfare rather than profit. The only means of helping those who are below the poverty line to increase their wage rate are interest-free loans and microfinance tools.